Effect of electron donating functional groups on corrosion inhibition of mild steel in hydrochloric acid: Experimental and quantum chemical study - Singh A.; Ansari K.R.; Haque J.; Dohare P.; Lgaz H.; Salghi R.; Quraishi M.A. (My University, 2025)
The corrosion inhibition performance of three triazine derivatives namely 4-((2-(5,6-diphenyl-1,2,4-triazin-3-yl)hydrazineylidene)methyl)-N,N-dimethylaniline (HT-1), 3-(2-(4 methoxybenzylidene) hydrazineyl)-5,6-diphenyl-1,2,4-triazine (HT-2) and 2-(2-(5,6-diphenyl-1,2,4-triazin-3-yl)hydrazineylidene)methyl)phenol (HT-3)on mild steel corrosion in1MHCl has been studied using gravimetric method, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, scanning electron microscopy (SEM), Density functional theory (DFT) and molecular dynamics simulation. The corrosion inhibition efficiencies at optimum concentration (80 mg L-1) are 98.6% (HT-1), 97.1%(HT-2) and 94.3% (HT-3) respectively at 308 K. The corrosion inhibition efficiency increases with increase in concentration and decreases with increase in temperature. The adsorption of HTs on the surface of mild steel obeyed Langmuir isotherm. Potentiodynamic polarization study confirmed that inhibitors are mixed type with cathodic predominance. SEM analysis confirmed that metal surface is smooth in presence of inhibitors. Quantum chemical calculation and Molecular dynamics simulation further support the experimental findings. © 2017 Taiwan Institute of Chemical Engineers